2012
DOI: 10.1080/09500340.2012.739712
|View full text |Cite
|
Sign up to set email alerts
|

Double spacing multi-wavelength L-band Brillouin erbium fiber laser with Raman pump

Abstract: A new multi-wavelength Brillouin erbium fiber laser (BEFL), which operates in the L-band region with double frequency Brillouin spacing, is demonstrated. This design uses a Raman pump (RP) and a piece of 2 km highly nonlinear fiber as a gain medium. The double frequency spacing is achieved by employing a dual ring configuration, which is formed by utilizing a four-port circulator that removes the odd-order Stoke signals. Twenty Stokes and seventeen anti-Stokes lines, which have optical signal to noise ratio (O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…From figures 4(a) and (b), it is also confirmed that by increasing the pump power, other Stokes lines can also be generated as long as the threshold power is exceeded. Since there is no reflection of the BP and the even Stokes lines in the backward direction, the optical signal-to-noise ratio (OSNR) is also improved in the backward direction as compared to the values that have been reported in previous works [16][17][18][19]. http://iopscience.iop.org/1555-6611/23/7/075108/article…”
Section: Experimental Set Upmentioning
confidence: 87%
See 1 more Smart Citation
“…From figures 4(a) and (b), it is also confirmed that by increasing the pump power, other Stokes lines can also be generated as long as the threshold power is exceeded. Since there is no reflection of the BP and the even Stokes lines in the backward direction, the optical signal-to-noise ratio (OSNR) is also improved in the backward direction as compared to the values that have been reported in previous works [16][17][18][19]. http://iopscience.iop.org/1555-6611/23/7/075108/article…”
Section: Experimental Set Upmentioning
confidence: 87%
“…A disadvantage of the MBFL is that the channel spacing, which is typically 0.08 nm (~10 GHz), is extremely hard to de-multiplex, thus rendering the MBFL unsuitable for practical applications. In order to address this problem, research has now explored the development of MBFLs with channel spacings that approximate double Brillouin shifts using two ring cavities [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%